Pulse transit time as an index of vascular reactivity - Sheamaa Ahmed Abdullah; Samar Imran Essa; Bassam Talib Al-Gailani (Journal of the Pakistan Medical Association, 2024)
Pulse transit time (PTT) is a non-invasive method for measuring arterial compliance and stiffness, which are excellent predictors of cardiovascular disease. This study aims to determine whether PTT can be used to precisely monitor vascular reactivity in response to changes in hand posture and whether the digital pulse wave index of time-to-maximum slope (TMS) is a suitable alternative to PTT. Fifteen healthy, 22-year-old males participated in the study. The PTT was monitored from electrocardiogram (ECG) to digital pulse wave (DPW), and the morphological variable TMS of the DPW wave was estimated in beat-tobeat intervals for the individuals while their arms were raised and dropped. The results demonstrated that the PTT increased significantly with elevating the hand, and the correlation probability of the second polynomial fitness equation neared infinite. In addition, the PTT significantly correlated (P<0.007) with the TMS of the DPW throughout the hand motions. The data indicate that PTT can represent local vascular responses during changes in hand position. In this study, we developed a new DPW index and suggest a TMS index as a viable substitute for PTT. Keywords: Cardiovascular, Electrocardiography, Pulse